DICOM Server: Aplicação para aquisição e encaminhamento automáticos de imagens médicas entre instituições de saúde - Diogo Filipe da Costa Ramalho (2014)
Medical Imaging is a specialty with great relevance for the diagnosis and treatment of numerouspathologies. Over the past decades, and following the same trend in other areas for technologicalevolution, imaging service has also evolved to take greater advantage of advances incomputer technology. At a time when the digital medical images are widely used, there are newchallenges to organize the collected information as well as access of data between institutions.Although currently a large part of health institutions possess systems that allow the storageand sharing of medical images, interoperability between applications is not yet a reality totallyachieved. The aim of this thesis is to study and develop a solution to simplify the exchange ofimaging information scattered across many institutions.This lack of interoperability among information systems affects the heath care provided to thepatient, which sometimes may be subject to repeat clinical evaluations and decisions based onincomplete information.The DICOM standard (Digital Imaging and Communication in Medicine) appeared in orderto improve interoperability between applications and set rules that would enable collaborationbetween them. It is widely used and is the preferred format for storing medical images.This thesis presents an application based on the DICOM standard, in order to perform forwardingand image acquisition between health institutions.The communication features such as procedures developed for routing and automatic acquisitionof medical images were detailed. The application is based on an architecture flexible, dynamicand adaptable to the needs. Desirable features for the application were tested by analysis of itsexecution time, and with the results of this analysis, it was concluded that the application displaysa satisfactory and stable performance fulfilling the proposed objectives.In summary, this application has an advantage by comprehending the DICOM standard whichis implemented and quite widespread in health institutions, making unnecessary the modificationof existing software.The application also provides functionality for forwarding and automatic acquisition of medical images, which could enable cooperation between entities dispersed and allow a more dynamic workflow.